Коллективный участник: правовое положение супруга участника общества с ограниченной ответственностью в соответствии с польским законодательством - Rytelewska, Aleksandra (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the legal status of spouse of the party of the limited liability company in the Polish law system. Presenting the selected topic the author focus on the legal regulation, ownership shares in the limited liability company in the context of marriage and ownership shares in the limited liability company after divorce.